E-SPAH: Aesthetic Innovation in UTHM’s Small-scale Rainwater Harvesting System - Mostaffa, Muhamad Faizal; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Kasim, Narimah; Mohd Noh, Hamidun; Md Yassin, Azlina (International Journal of Integrated Engineering, 2021)
A rainwater harvesting (RWH) system is a method of storing rainwater for future purposes. Universiti Tun Hussein Onn Malaysia (UTHM) has implemented this effort on some of the buildings in Main Campus, Parit Raja. However, this system has the weakness that caused the RWH system to stop from appropriately operated. Some of the RWH components are damaged because the design is not thought of thoroughly in the long term. Furthermore, the Main Campus is highly dependent on the treated water supply that caused a high amount of utility bills. Therefore, this study has highlighted the need to analyse the existing small scale RWH system in UTHM’s Main Campus, identify the suitable tank form for UTHM’s Main Campus small scale RWH system, and suggest a small scale RWH system’s design for outdoor purposes in Main Campus UTHM. This study has been carried out by using literature review, interview session and observation. The result shows that the small scale RWH system in UTHM Main Campus has a few strengths, weaknesses, opportunities, and threats. Cylindrical tank form is chosen to design the university’s small scale RWH system. A modular RWH system with the number of tanks installed based on rainwater catchment area is suggested and named E-SPAH, a concept of RWH system that emphasises efficiency and outdoor usage. Perhaps this study would help future researchers, universities, and contractors guide future small-scale rainwater harvesting systems for outdoor purposes in UTHM’s Main Campus.